Making seed pay - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2025)
This documentary showcases the role of farmers’ associations of cassava and sweetpotato seed producers in strengthening the profitable seed business of these crops in Tanzania. It highlights how the associations are organised and operate in delivering services to their members to enhance seed production and marketing. A key purpose of the documentary is to demonstrate to farmer seed producers elsewhere how associations can strengthen the scale and sustainability of seed production for vegetatively propagated crops